Acute respiratory distress associated with a nasopharyngeal foreign body in a seven‐month‐old French bulldog. Issue 2 (4th January 2017) - Duplan, Florent; Gelens, Hans; Amsellem, Pierre
Abstract : This report describes an acute respiratory distress due to an unusual underlying disorder in a dog of a typical breed predisposed to the brachycephalic obstructive airway syndrome. The physical examination revealed a stertorous breathing compatible with a nasopharyngeal disorder. Rhinoscopy and CT scan revealed a mass‐like structure obstructing both choanae. The foreign body was successfully removed by a ventral rhinotomy as an endoscopic‐assisted procedure failed to dislodge it. A follow‐up examination 14 days later documented a complete resolution of the respiratory signs. One could have expected that brachycephalic syndrome was the source of dyspnoea. However, knowledge of the history combined with thorough evaluation of the dog's airways allowed the diagnosis of a nasopharyngeal foreign body. Practically, the authors recommend complete airway examination including thoracic and cervical radiographs, direct evaluation of larynx, bronchoscopy and retroflexed rhinoscopy to assess the nasopharynx in all dogs with dyspnoea associated with upper airway obstruction.